Identification of Flow Zones Inside and at the Base of a Uranium Mine Tailings Dam Using Geophysics - Arcila, Erika Juliana Aldana [UNESP]; Moreira, César Augusto [UNESP]; Camarero, Pedro Lemos; Casagrande, Matheus Felipe Stanfoca [UNESP] (Springer Nature, 2021)
Potential problems related to a tailings dam’s stability are a matter of concern, especially where structural failure might endanger nearby communities and the environment. The Osamu Utsumi mine, located in the State of Minas Gerais, is currently not operating. The rock-soil tailings dam has water upwelling downstream in the bedrock, with water flux confined to rock fractures. This research was conducted to identify possible flux zones in the base of the dam using DC resistivity and electrical resistivity tomography (ERT). The data acquisition consisted of five ERT lines with 6 m of spacing between electrodes, using a Schlumberger array. The results are presented by 2D and 3D geophysical models comprising measured and processed resistivity values. It was possible to identify a low resistivity zone (5–20 Ωm), whose structural continuity indicates water infiltration in the bedrock under the dam. Moreover, the results do not indicate that erosion is taking place in the interior of the dam, reducing the risk of geotechnical instability and failure of physical integrity.
Identificación Mediante Geofísica de Zonas de Flujo en el Interior y en el Basamento de una Presa de Colas de una Mina de Uranio
Keywords: 3D model; DC resistivity; ERT; Mining